FOTOTERAPI BERPENGARUH TERHADAP PRAKTIK PEMBERIAN ASI EKSKLUSIF DI YOGYAKARTA - Ida Nursanti; Dwi Susanti (LPPM Politeknik Kesehatan Karya Husada Yogyakarta, 2014)
Background: It is evident that exclusive breastfeeding is good for babies; however, the success can come to a failure when the babies are sick. Many babies return to the hospital for treatment due to neonatal jaundice. Phototherapy can hamper mothers to breastfeed their babies and cause anxiety that ultimately affects the lactating process.Babies receiving phototherapy can suffer dehydration; however, this effect can be prevented by administrating sufficient liquid as an alternative when breast milk is inadequate.Objective: To determine the effects of phototherapy and other factors against breastfeeding to babies receiving phototherapy.Methods: This was an observational study with a prospective cohort study design. Samples were taken by way of purposive sampling, amounted to 124 pairs of mother-baby. The instrument was monitoring sheets. The data were analyzed using univariable and bivariable analysis with chi-square statistical test, significance level of less than 0.05 and CI 95%.Results: There were effects of phototherapy on breastfeeding with a p value of0.04, an R2 value of 1.4 and CI 95% 0.96-2.06. Another factor affecting breastfeeding was maternal education (p=0.00, RR 1.6 and CI95% 1.13-2.37) while age (p=0.35), employment (p=0.15), experience (p=0.77) and family support (p=0.05) did not contribute a significant relationship.Conclusion: Babies receiving phototherapy with a longer period of time had a higher risk of failing to have full-breastfeeding by 1.4 times than those with a shorter period of time. Mothers with higher level of education were likely to have a 1.6 greater chance of being successful in the provision of exclusive breastfeeding while the babies received phototherapy.